Spirit - Kemmerer, Brigid (Kemmerer, Brigid. Elemental series., 2013)
"Hunter Garrity just wants to be left alone. He's learned the hard way that his unusual abilities come at a price. And he can't seem to afford any allies. He's up to his neck in hostiles. His grandfather, spoiling for a fight. The Merrick brothers, who think he ratted them out. Calla, the scheming psycho who wants to use him as bait. Then there's Kate Sullivan, the new girl at school. She's not hostile. She's bold. Funny. Hot. But she's got an agenda, too"--P. [4] of cover.